Textual criticism of the Hebrew Bible - Tov, ʿEmanuʾel (Fortress Press, 2012)
"Since its initial publication, Textual Criticism of the Hebrew Bible has established itself as the indispensable authoritative textbook and reference on the subject. In this thoroughly revised third edition, Emanuel Tov has incorporated the insights of the last ten years of scholarship, including new perspectives on the biblical texts among the Dead Sea Scrolls, all of which have now been published. Here are expanded discussions of the contribution of textual criticism to biblical exegesis and of the role of scribes in the transmission of the text. The introduction and references throughout the book have been thoroughly revised with the beginning student of textual criticism in mind" -- Publisher description